DEVELOPING INSTRUCTIONAL VIDEO FOR ONLINE LITERAL READING COURSE - Ni Made Yuniari; I Gusti Ayu Indah Triana Juliari (Language and Education Journal Undiksha, 2020)
AbstractThis research is R & D. The process of development has been done by using ADDIE model which has five stages of development namely; analysis, design, development, implementation, and evaluation. In this research, the ADDIE model was modified by the researcher. It modified from the analysis until the development stage, because the purpose of this research is limited to develop and produce the Instructional Video for online literal reading course which is appropriate used based on the assessment of the experts. The experts in this research were the subject matter experts, and the learning media expert. Data collection instrument used in this research were validation sheets which were given to experts. Based on the validation result on all aspects namely content, design, pedagogy, and the practicability aspect can be found that the highest average percentage is the practicability aspect (93%) and it is categorized as valid. It can be concluded that the Instructional Video for online literal reading course is appropriate used as the teaching media for second semester students of English Language Education at Dwijendra University. Besides, the instructional video is hoped to be a solution for the lecturers in presenting the attractive materials which can increased the students’ motivation in learning reading. However, in future the researcher needs to continue the other steps of the ADDIE model such as the implementation and the evaluation in order to find out the better result of the development of instructional video.Keywords: Developing Instructional Video, online course, literal reading